Ecto- and arbuscular mycorrhizal symbiosis can induce tolerance to toxic pulses of phosphorus in jarrah (Eucalyptus marginata) seedlings - Kariman, Khalil; Barker, Susan J.; Finnegan, Patrick M.; Tibbett, Mark (Springer Science Business Media, 2014)
In common with many plants native to low P soils, jarrah (Eucalyptus marginata) develops toxicity symptoms upon exposure to elevated phosphorus (P). Jarrah plants can establish arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) associations, along with a non-colonizing symbiosis described recently. AM colonization is known to influence the pattern of expression of genes required for P uptake of host plants and our aim was to investigate this phenomenon in relation to P sensitivity. Therefore, we examined the effect on hosts of the presence of AM and ECM fungi in combination with toxic pulses of P and assessed possible correlations between the induced tolerance and the shoot P concentration. The P transport dynamics of AM (Rhizophagus irregularis and Scutellospora calospora), ECM (Scleroderma sp.), non-colonizing symbiosis (Austroboletus occidentalis), dual mycorrhizal (R. irregularis and Scleroderma sp.), and non-mycorrhizal (NM) seedlings were monitored following two pulses of P. The ECM and A. occidentalis associations significantly enhanced the shoot P content of jarrah plants growing under P-deficient conditions. In addition, S. calospora, A. occidentalis, and Scleroderma sp. all stimulated plant growth significantly. All inoculated plants had significantly lower phytotoxicity symptoms compared to NM controls 7days after addition of an elevated P dose (30mg Pkg−1 soil). Following exposure to toxicity-inducing levels of P, the shoot P concentration was significantly lower in R. irregularis-inoculated and dually inoculated plants compared to NM controls. Although all inoculated plants had reduced toxicity symptoms and there was a positive linear relationship between rank and shoot P concentration, the protective effect was not necessarily explained by the type of fungal association or the extent of mycorrhizal colonization.